Avaliação de impactos da cadeia produtiva em aeroportos: o caso de Congonhas - Silva, Paulo Diego D' Ovídio (2012)
Over time, the business grossed airport beyond its traditional functions, such as transporting passengers and cargo, commercial functions, with the inclusion of shopping malls, cinemas, food courts, among others. Thus, several developments aids such as logistics companies, car rental, travel agencies and even residential neighborhoods, occupied in a disordered manner the airport surroundings, causing adverse impacts to their neighborhood. Aiming to remedy this and other undesirable consequences of development at any cost, which prevailed in recent decades, there was Law Project 181/89, which led the Estatuto da Cidade. Sanctioned in 2001, the Estatuto represented a major breakthrough with regard to planning and urban development, bringing an instrument to help assess environmental impacts at local level: the Impact of Neighborhood, which is designed the housing projects, institutional or commercial for which there is no requirement for the studies. This paper proposes a methodological framework for prediction, assessment and evaluation of impacts due to construction and operation of enterprises that make up the production chain airport, considering the neighborhood impacts arising from the implementation and operation of the Airport of Sao Paulo-Congonhas, which do not considered in environmental impact studies. At first, a literature review was conducted to understand the specifics of the study area, passing by the physicals, socials and economics attributes. This process was followed by field work, where photographic records were made, the identification of the production chain linked to the airport and the main impacts that it causes the local neighborhood. Then the collected data were used to compose cartographic representations, showing areas of occurrence for each impact raised, and the participation of each sector that makes up the production chain in the generation of such impacts. 8 After performing the above-mentioned procedures, it was concluded that the most significant impacts to the neighborhood were vehicles parked on uneven areas (such as sidewalks, vacant properties and on traffic routes) and the generation of noise, from the production structure, the mass circulation of vehicles and the airport itself. Among the groups of enterprises studied, it was observed that companies facing the logistics industry (cargo) and the airlines appear as the most striking, being the main generators of both the impacts described above, giving worse quality of life of local people.